PENGGUNAAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA - Hasanah, Euis (IKIP Siliwangi Bandung, 2021)
This study aims to answer problem formulation: whether the Realistic Mathematics Education approach can increase activeness and learning outcomes on PLSV material. The success indicated learning outcomes, namely 72.38 with 76.19% classical completeness and percentage of students' activity learning in each cycle. This study is a classroom action research. The research subjects were students of VII-B at SMP Negeri 3 Rancaekek which totally were 30 students. Data were collected by observation, documentation and tests. The collected data were analyzed using descriptive analysis and calculating the average score, the percentage of activity learning and the students' classical learning completeness. Based on the research results, it can be concluded that the class average from cycle I to cycle II increased by 4.53 points. The average of student learning outcomes has reached minimum completeness criteria (KKM). Classical learning completeness increased by 14.29%. In the activity learning, the percentage increase 13%. However, Learning by the Realistic Mathematics Education approach can increase the activeness and learning outcomes of students.Â